1991
DOI: 10.1111/j.1432-2277.1991.tb01953.x
|View full text |Cite
|
Sign up to set email alerts
|

31P-NMR study of cardiac preservation: St. Thomas' Hospital cardioplegic solution versus UW preservation solution

Abstract: Abstract. Ex vivo cardiac preservation was evaluated by measuring the catabolism of high‐energy phosphate (ATP and creatine phosphate, CrP) using 31P‐NMR spectroscopy. After cardioplegic arrest St. Thomas' Hospital cardioplegic solution (group A), and University of Wisconsin (UW) preservation solution (group B) were tested. The hearts were mounted in the 4.7 T horizontal bore magnet of the NMR spectrometer and were continuously perfused with the test solution under 25 cm H2O pressure for 6 h at 10°C. Peak hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Another animal study showed a strong influence of nutritional status on the "P-MR liver spectrum [106]. Similar results were seen in the human body too, especially in human hearts [4,70] and kidneys [15]. In a recent publication, Wolf et al reported their own experience with MRS on human livers during cold storage.…”
Section: Atp Cofitent Of the Liver: Spectroscopymentioning
confidence: 59%
“…Another animal study showed a strong influence of nutritional status on the "P-MR liver spectrum [106]. Similar results were seen in the human body too, especially in human hearts [4,70] and kidneys [15]. In a recent publication, Wolf et al reported their own experience with MRS on human livers during cold storage.…”
Section: Atp Cofitent Of the Liver: Spectroscopymentioning
confidence: 59%